GC-MS PROFILE AND CHEMOPROTECTIVE EFFECT OF Cinnamomum zeylanicum BARK ESSENTIAL OIL AGAINST TRIPLE-NEGATIVE BREAST CANCER CELL LINE MDA-MB-231 (Applied Biological Research, 2025)
Cinnamomum zeylanicum Blume (Lauraceae) bark is one of the most important spices used to enhance the taste and flavour of Indian foods. Besides its use as a spice, C. zeylanicum bark possesses antioxidant, antimicrobial, antifungal, anti-inflammatory, and chemoprotective properties. The present study aimed to characterize the key chemical constituents of C. zeylanicum bark essential oil and to determine its chemoprotective effect against triple-negative breast cancer (TNBC) cells. The chemical composition of C. zeylanicum bark essential oil was determined using gas chromatography–mass spectrometry (GC–MS). The analysis identified 29 chemical compounds, among which (E)-cinnamaldehyde (69.89%), eugenol (14.27%), δ-cadinene (2.80%), and (Z)-caryophyllene (2.33%) were the major constituents. The essential oil exhibited concentration- and time-dependent inhibition of TNBC (MDA-MB-231) cells. A concentration of 15.62 μL mL⁻¹ produced maximum inhibition of MDA-MB-231 cells, amounting to approximately 90.6%. The aroma profile and significant in vitro anticancer activity of C. zeylanicum bark essential oil provide a scientific basis for its potential use as a cancer remedy
Keywords: Aroma profile; breast cancer; Cinnamomum zeylanicum; cinnamon; essential oil; TNBC